Historical analysis of Santa Gertrudes/SP ceramic pole: it's relevance in Cordeiropolis/SP - Vieira, Paulo Henrique [UNESP] (Univ Federal Mato Grosso, 2022)
The analysis and interpretation of the relationship between man and nature is a relevant theme for geographers that focus on the environmental issue, in order to help and provide subsidies for the implementation of territorial planning. In this context, the objective of this work was the socioenvironmental analysis of the Santa Gertrudes Ceramic Pole (PCSG), with emphasis on the municipality of Cordeiropolis/SP. This industrial complex is located in the center-east region of the state of Sao Paulo (Limeira/SP microregion), which is composed of 8 municipalities, including Cordeiropolis/SP and Santa Gertrudes/SP. The local ceramic industries have been causing numerous social and environmental impacts: air, water and noise pollution, disruption of automobile traffic routes, vegetation removal, among other problems. Aiming to achieve the general objective, the work uses empirical analysis and in addition, proposed the following methodological approach: bibliographic and data survey; office work (organization of references and data, preparation of thematic maps); and fieldwork in Cordeiropolis/SP. Currently, the environmental issue and its relation to economic activities is a challenge, as it involves several interests, in which the priority is always economic activity. Thus, this work analyzes the mining activity in Cordeiropolis/SP, which compromises the preservation and conservation of nature, as well as proposes measures to minimize the impacts of such activitydo
Keywords: Environmental issue; Ceramic industries; Environmental impacts